2004
DOI: 10.1590/s1519-566x2004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Relação predador: presa de Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) para o controle do pulgão-verde em genótipos de sorgo

Abstract: -The use of host plant resistance associated with biocontrol agents may be a viable alternative to Schizaphis graminum (Rondani) control in sorghum. This work aimed to study different predator:prey ratios on genotype resistant (TX 430 x GR 111), moderately resistant (GB 3B) and susceptible (BR 007B) for the aphid control by the predator Chrysoperla externa (Hagen). Thus, the lacewings were released at the predator:prey ratios of 1:5; 1:10; 1:25 and 1:50 under greenhouse conditions. The genotype TX x GR 111 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Among the studies that have assessed the predatory efficiency and larval survival of C. externa associated with pest arthropods (Figueira and Lara, 2004;Barbosa et al, 2008;Gamboa et al, 2016, for example), we did not find any that addressed the effect of the age of the prey. We found high predatory efficiency of second-instar larvae of C. externa toward M. rosae, regardless of aphid age.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Among the studies that have assessed the predatory efficiency and larval survival of C. externa associated with pest arthropods (Figueira and Lara, 2004;Barbosa et al, 2008;Gamboa et al, 2016, for example), we did not find any that addressed the effect of the age of the prey. We found high predatory efficiency of second-instar larvae of C. externa toward M. rosae, regardless of aphid age.…”
Section: Discussionmentioning
confidence: 62%
“…These results indicate a negative relationship between the predator:prey ratio and the larval survival variable but a positive relationship between this ratio and predatory efficiency. In general, high predator:prey ratios are more efficient at pest control (Zaki et al, 1999;Figueira and Lara, 2004;Opit et al, 2004;Rahman et al, 2011;Saleh et al, 2017) due to the higher probability of encounters between species, as well as the competitive effect among the conspecifics for the available food (Souza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…, 2001). Figueira and Lara (2004) observed that C. externa reduced the population of the green aphid Schizaphis graminum (Rondani) (Hemiptera: Aphididae) in genotypes of sorghum at the ratio of 1 larvae of the chrysopod to 10 aphids. Ribeiro et al (2007) reported the predatory aptitude of C. externa larvae at different instances on the citrus leafminer of the Citrus Phyllocnistis citrella (Station) (Lepidoptera: Gracillariidae), and found that the highest larvae predation index occurred with third instance, which consumed 43,2% of third instance caterpillars.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Chrysopidae, predators of many pests arthropods from different cultures. Many of the chrysopods, such as Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) stand out, occurring naturally in crops of economic interest (FONSECA; CARVALHO; SOUZA, 2001), among them the melon crop (FREITAS; PENNY, 2001) Figueira and Lara (2004). observed that C. externa reduced the population of the green aphid Schizaphis graminum (Rondani) (Hemiptera: Aphididae) in genotypes of sorghum at the ratio of 1 larvae of the chrysopod to 10 aphids Ribeiro et al (2007).…”
mentioning
confidence: 99%